New 1-(3-Nitrophenyl)-5,6-dihydro-4H-[1,2,4]triazolo[4,3-a][1,5]benzodiazepines: Synthesis and Computational Study - Lidija Kosychova; Antanas Karalius; Zita Staniulytė; Romualdas Aleksas Sirutkaitis; Algirdas Palaima; Audrius Laurynėnas; Žilvinas Anusevičius (Molecules, 2015)
Triazole derivatives constitute an important group of heterocyclic compounds have have been the subject of extensive study in the recent past. These compounds have shown a wide range of biological and pharmacological activities. In this work, new fused tricyclic 1-(3-nitrophenyl)-5,6-dihydro-4H-[1,2,4]triazolo[4,3-a][1,5]-benzodiazepines have been synthesized by the thermal cyclization of N'-(2,3-dihydro-1H-1,5-benzodiazepin-4-yl)-3-nitrobenzohydrazides. After screening ethanol, toluene and 1-butanol as solvents, butanol-1 was found to be the best choice for the cyclization reaction in order to obtain the highest yields of tricyclic derivatives. The chemical structures of the synthesized compounds were elucidated by the analysis of their IR, 1H- and 13C-NMR spectral data. For tentative rationalization of the reaction processes, the global and local reactivity indices of certain compounds, taking part in the reaction pathway, were assessed by means of quantum mechanical calculations using the conceptual density functional theory (DFT) approach. This work could be useful for the synthesis of new heterocyclic compounds bearing a fused triazole ring.